Joint Optimization of Radar Assignment and Resource Allocation for Target Tracking in Phased Array Radar Network - Shi, Chenguang; Shi, Zhao; Salous, Sana; Zhou, JianJiang (Proceedings of the IEEE Radar Conference, 2021)
This paper proposes a joint optimization strategy of radar assignment and resource allocation for target tracking in phased array radar network (PARN). The main purpose of the proposed strategy is to coordinate the radar assignment, transmit power, and dwell time of multiple radars to improve the target tracking accuracy, subject to several transmit resource budgets. The analytical expression for the Bayesian Cramér-Rao lower bound (BCRLB) is derived and adopted as the objective function to quantify the target tracking performance. Subsequently, a fast and effective two-step solution algorithm, which incorporates the interior point method and cyclic minimization framework, is proposed to solve the resulting optimization problem. Simulation results are provided to demonstrate the effectiveness of the developed scheme.